Induction of Oxidative Stress and Ferroptosis in Triple-Negative Breast Cancer Cells by Niclosamide via Blockade of the Function and Expression of SLC38A5 and SLC7A11 - Marilyn Mathew; Sathish Sivaprakasam; Gunadharini Dharmalingam-Nandagopal; Souad R. Sennoune; Nhi T. Nguyen; Valeria Jaramillo-Martinez; Yangzom D. Bhutia; Vadivel Ganapathy (MDPI AG, 2024)
The amino acid transporters SLC38A5 and SLC7A11 are upregulated in triple-negative breast cancer (TNBC). SLC38A5 transports glutamine, methionine, glycine and serine, and therefore activates mTOR signaling and induces epigenetic modifications. SLC7A11 transports cystine and increases the cellular levels of glutathione, which protects against oxidative stress and lipid peroxidation via glutathione peroxidase, a seleno (Se)-enzyme. The primary source of Se is dietary Se-methionine (Se-Met). Since SLC38A5 transports methionine, we examined its role in Se-Met uptake in TNBC cells. We found that SLC38A5 interacts with methionine and Se-Met with comparable affinity. We also examined the influence of Se-Met on Nrf2 in TNBC cells. Se-Met activated Nrf2 and induced the expression of Nrf2-target genes, including SLC7A11. Our previous work discovered niclosamide, an antiparasitic drug, as a potent inhibitor of SLC38A5. Here, we found SLC7A11 to be inhibited by niclosamide with an IC50 value in the range of 0.1-0.2 μM. In addition to the direct inhibition of SLC38A5 and SLC7A11, the pretreatment of TNBC cells with niclosamide reduced the expression of both transporters. Niclosamide decreased the glutathione levels, inhibited proliferation, suppressed GPX4 expression, increased lipid peroxidation, and induced ferroptosis in TNBC cells. It also significantly reduced the growth of the TNBC cell line MB231 in mouse xenografts.